Wieś Siedlce w ziemi łukowskiej - WOŹNICA, Kamila (Historia i Świat, 2014)
Although it has been a settlement since the ninth century, the sources regarding Siedlce before it was granted the town charter are few. The town was situated at the northern edge of the Łuków district, which was a part of the Kingdom of Poland. . The first houses were (found?) on the grounds of the present day palace and the town hospital. The first mention of Siedlce in the written records comes from 1441, when Wojciech of Michów from the Rawicz family exchanged his property with that of his relative Elżbieta, wife of Jan from Oleksów. He gave her half of Siedlce as well as half of Golice, Wola Siedlecka and Wola Golicka in the Łuków district and received in return half of Rudno and half of Składów in the Lublin district. . Elżbieta was in all probability the grandmother of Daniel Gniewosz Siedlecki, the owner of Siedlce at the turn of 16th century. In the early 16th century, Daniel Gniewosz’s properties, and subsequently his son’s, Stanisław Gniewosz’s, properties, flourished. In addition to Siedlce, they owned between ten and twenty other villages and ironworks by the Muchawka and Liwiec rivers. In 1532, a parish was established and a church under the name of the Blessed Virgin Mary and Stanislaus of Szczepanów, the bishop and martyr, was erected. Another success of Stanisław Siedlecki was the granting of the town charter by Sigismund I the Old in 1547 on the basis of which a e town, named Nowa Siedlcza, was established a little further west from the village.